GAMBARAN KARIES GIGI ANAK NELAYAN USIA 12 TAHUN DI DUSUN PABEAN, DESA SANGSIT, KABUPATEN BULELENG TAHUN 2013 - I Made Karmawan Putra; I Nyoman Gejir; Ni Made Widhiasti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
Background : The prevention of dental carries can be done by the opplication of topical fluor which is a safe methode of prevention. The substance of the application which brings good result is Calsium Fluoride (CaF2).